Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.18502/ijpho.v9i4.1574
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Caregiver Burden among Parents of Children with Cancer

Abstract: Background: Cancer is one of the most common diseases in children. Cancer in children can cause many problems for parents, and impose heavy care burden on them, which can lead to negative health consequences. The aim of this study was to determine caregiving burden and relevant influential factors among parents of children with cancer. Materials and Methods: This cross-sectional descriptive study was done on 125 parents of children with cancer in oncology department of Shohada Hospital, Tehran, Iran, dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 0 publications
1
10
1
2
Order By: Relevance
“…This cross-sectional study was conducted to determine the level of care burden and its related factors in the caregivers of children with cancer in Iran. In line with previous studies [ 4 , 15 , 17 , 18 , 28 ], most caregivers of children with cancer endured moderate to high care burden. Cancer diagnosis and treatment cause many psychological problems for the family of a child with cancer.…”
Section: Discussionsupporting
confidence: 88%
“…This cross-sectional study was conducted to determine the level of care burden and its related factors in the caregivers of children with cancer in Iran. In line with previous studies [ 4 , 15 , 17 , 18 , 28 ], most caregivers of children with cancer endured moderate to high care burden. Cancer diagnosis and treatment cause many psychological problems for the family of a child with cancer.…”
Section: Discussionsupporting
confidence: 88%
“…This study's result, which stands in contrast to the literature, is thought to be due to the fact that only anxiety towards coronavirus was measured rather than overall anxiety. In addition, this study is not compatible with Ahmadi et al’s ( 2019 ) study may be due to the different age groups of the children.…”
Section: Discussioncontrasting
confidence: 93%
“…Ozdemir Koyu and Tas Arslan ( 2021 ) identified no relationship between the burden of caregiving and children's ages. However, Ahmadi et al ( 2019 ) identified a relationship between parental age, child age and parental care burden. Moreover, studies revealed a positive correlation between the anxiety and care burden of parents of children with cancer (Köse et al, 2019 ; Ozdemir Koyu & Tas Arslan, 2021 ; Wang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies evaluating the burden of care among parents of children with cancer and chronic diseases, the Zarit Burden Interview (ZBI), the Caregiver Burden Scale (CBS), and the Caregiver Burden Inventory (CBI) are widely used (Ahmadi et al, 2019; Mohammadi et al, 2020; Salvador et al, 2015; Santo-Espirito et al, 2011; Özdemir et al, 2009). Current CBSs used in these studies have largely been developed for family caregivers of adults with dementia or stroke, or with elderly people.…”
mentioning
confidence: 99%